2017
DOI: 10.4236/ojanes.2017.711039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Liposomal Bupivacaine Infiltrated into the Posterior Capsule for Postoperative Analgesia after Total Knee Arthroplasty—A Randomized Double Blind Clinical Trial

Abstract: Achieving adequate control of postsurgical pain remains a challenge in patients undergoing Total Knee Arthroplasty (TKA). The objective of this study was to assess if liposomal bupivacaine injected into the posterior capsule, in combination with a femoral nerve block and multimodal pain control regimen, would result in better pain control. The two groups were similar with regards to demographics and method of intraoperative anesthesia. Infiltration into the posterior capsule with liposomal bupivacaine had sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…11 Garg et al did а study to assess the effectiveness of LIA (buрivасаine) given into the роsteriоr сарsule аlоng with FNB and concluded that posterior capsular infiltration aided in relieving the post-operative pain after TKA. 12 In our study, it was observed that values of VAS were significantly lower in Group A when compared to Group B at rest and on movement, at different time frames. It depicts improved and better pain control with posterior capsular infiltration.…”
Section: Discussionmentioning
confidence: 44%
“…11 Garg et al did а study to assess the effectiveness of LIA (buрivасаine) given into the роsteriоr сарsule аlоng with FNB and concluded that posterior capsular infiltration aided in relieving the post-operative pain after TKA. 12 In our study, it was observed that values of VAS were significantly lower in Group A when compared to Group B at rest and on movement, at different time frames. It depicts improved and better pain control with posterior capsular infiltration.…”
Section: Discussionmentioning
confidence: 44%